PENERAPAN PENDEKATAN SOCIO-SCIENTIFIC ISSUES BERBANTUAN E-LKPD PADA MATERI ZAT ADITIF UNTUK MENINGKATKAN LITERASI SAINS - Khasanah, Sarah Uswatun; Setiawan, Beni (PENSA E-JURNAL: PENDIDIKAN SAINS, 2022)
This study aimed to describe the increase of students’ scientific literacy on additive substances using socio-scientific issues approaches assisted by electronic worksheets. This study was a pre-experimental design with one group pretest-posttest as a research design. Samples in this study were 37 students of VIII-C grade in SMPN 31 Surabaya. The data were collected using observation, questionnaires, and tests. The implementation of learning obtained high results with very good categories in the first and second meetings. The increase in students’ scientific literacy was analyzed using paired t-test and N-Gain test. The paired t-test result indicated the treatment’s effect on student scientific literacy. The N-Gain test result obtained a value of 0,85 indicating an increase in the high category. The results of the student responses got a high percentage, meaning that students responded very well to the electronic worksheets. Based on the result, it can be concluded that the socio-scientific issues approach assisted by electronic worksheets could improve students’ scientific literacy.